Current therapy and recent advances in the management of retinoblastoma - Rachna Meel; Venkatraman Radhakrishnan; Sameer Bakhshi (Indian Journal of Medical and Paediatric Oncology)
Retinoblastoma is the most common intraocular malignancy in children. The survival of retinoblastoma patients and visual outcome has improved dramatically in the developed world. This can be attributed to early tumor recognition and advances in the management of retinoblastoma. Chemoreduction followed by adjuvant consolidative treatment has replaced external beam radiotherapy as the primary modality of treatment for intraocular retinoblastoma. Further, histopathological high-risk factors have been identified in enucleated eyes, allowing use of prophylactic chemotherapy to take care of possible micrometastasis. The survival in case of extraocular retinoblastoma is still low, and the reported survival rate ranges between 50% and 70%. In developing countries, the overall survival of retinoblastoma patients remains low, primarily due to a delayed presentation, resulting in larger proportions of extraocular disease compared with the developed world, where majority of the disease is intraocular. Greater efforts need to be directed toward early tumor recognition in order to improve the survival of retinoblastoma patients in the developing world. In this article, we provide an overview of the current clinical management of retinoblastoma.